The Effects of Price, Income, and Household Characteristics on Ultra-Processed Food Consumption In Jakarta, Indonesia - Atika Putri Syatira; Ekaria Ekaria (Pusat Penelitian dan Pengabdian kepada Masyarakat Politeknik Statistika STIS, 2020)
During the 2010s, ultra-processed food consumption in Indonesia increases and leads to high rates of obesity and chronic non-communicable diseases. DKI Jakarta has the highest ultra-processed food consumption and obesity prevalence in Indonesia. Therefore, raw data from “Core” and “Consumption and Expenditure” modules of March 2019 Susenas (Indonesia National Socioeconomic Survey) are analysed to examine ultra-processed food consumption and how economic factors and household characteristics affect it in Jakarta. The analysis is conducted using M-estimation robust regression due to a large number of influential outliers in the data. The research sample is divided into three classes based on daily per capita expenditure. The results show that ultra-processed food consumption increases with income class. Higher ultra-processed food consumption occurs in households that pay higher price for ultra-processed food, have higher per capita income, have more children or adolescents, and have working female household head or wife. For Class 3 households, formal sector households consume more ultra-processed food than informal sector households. While for Class 1 households, households with female household head or wife with senior high school degree or above consume more ultra-processed food than households with female household head or wife with junior high school degree or below.